Superconducting properties of nanostructured microhelices; Journal of Physics: Condensed Matter; Vol. 29, iss. 39 - Fomin V. M. Vladimir Mikhaylovich; Rezaev R. O. Roman Olegovich; Levchenko E. A. Evgeny Anatolievich; Grimm D.; Schmidt O. G. Oliver (2017, 2017)
Title screen